Thiolate/Disulfide Based Electrolytes for p-type and Tandem Dye-Sensitized Solar Cells. (10th November 2015) - Powar, Satvasheel; Bhargava, Rishabh; Daeneke, Torben; Götz, Günther; Bäuerle, Peter; Geiger, Thomas; Kuster, Simon; Nüesch, Frank A.; Spiccia, Leone; Bach, Udo
Abstract: This article presents the first report of a tandem dye-sensitized solar cell employing optically transparent, non-corrosive metal-free thiolate/disulfide based electrolytes and a set of sensitizers with complementary absorption spectra. Sodium 1-phenyl-1H-tetrazole-5-thiolate and its reduced form 5, 5′-dithiobis(1-phenyl-1H-tetrazole) (thiolate/disulfide) were used as redox mediators for photocathodic dye-sensitized solar cells (p-DSCs), yielding higher open circuit voltages (285 mV) compared to the more commonly used iodide-based redox couple (226 mV). The herein achieved efficiencies of p-DSCs (0.51 %) and pn-DSCs (1.33 %) employing the thiolate/disulfide-based electrolytes were comparable to p-DSCs and pn-DSCs employing conventional iodide-based electrolytes (0.44 % and 1.19 %).